Primary dysmenorrhea and postural control: Is it a problem only during menstruation? - CAN, HİLAL BAŞAK (ELSEVIER IRELAND LTD, 2021)
Background: The effects of the menstrual cycle and primary dysmenorrhea (PD) on phase-related cognitive and physical functions are controversial. This study was carried out to examine whether women with PD showed a different physical function or dual-tasking response than women without PD at times other than menstruation. Methods: Women with or without PD were recruited for the study. Individuals assessed on the first day of the menstruation and the day they reported themselves as well being (feeling good day-FGD). Zebris ? FDM Type Force Platform was used to evaluate postural stability. Individuals have were asked to perform to a 3-step balance test protocol; the first session: comfortable upright standing; the second session: standing with a motor task; the third session: standing with a cognitive task (counting backward). Correctly calculated numbers were also recorded. Results: The number of correct answers given by individuals during the cognitive dual-task was similar on the first day of menstruation and FGD (p 0,05). In the assessments performed on the first day of menstruation, there was no difference in any parameters between the groups (p 0.05). In the measurements made on FGD day with the cognitive task; there was a difference between the groups (p < 0,05). Individuals with PD had higher postural sway. Significance: This study showed that the primary dysmenorrhea is not only a problem for females during menstruation, primary dysmenorrhea causes impaired ability of the individual to perform dual-tasking and continuously affects postural stability.
Keywords: Primary dysmenorrhea; Menstrual cycle; Postural balance; Cognition; Dual-tasking behavior; Pain; HEART-RATE-VARIABILITY; QUALITY-OF-LIFE; SELF-PERCEPTION; CYCLE; WOMEN; PAIN; ESTROGEN; PHASE; PERFORMANCE; STABILITY